Palladium-Catalyzed Decarboxylation of Benzyl Fluorobenzoates - Makida, Yusuke; Matsumoto, Yasutaka; Kuwano, Ryoichi (Synlett, 2017)
The decarboxylation of benzyl fluorobenzoates has been developed by using the palladium catalyst prepared in situ from Pd(η3-allyl)Cp and bulky monophosphine ligand XPhos. The catalytic reaction afforded a range of fluorinated diarylmethanes in good yields with broad functional-group compatibility. The substrates were readily synthesized by condensation of the corresponding benzoic acid with benzyl alcohol. Therefore, the transformation is formally regarded as a cross-coupling reaction between fluorine-containing benzoic acids and benzyl alcohols.
Keywords: decarboxylation; benzylation; palladium catalyst; diarylmethane; fluoroarene; C–O activation; benzyl palladium intermediate